Trade union representation for new forms of employment. Issue 3 (September 2019) - Schlachter, Monika
Defining the personal scope of application of the right to be represented by a trade union for collective bargaining purposes starts by defining the notion of employee/worker on whose behalf the conclusion of collective agreements is not disputed. In the German legal system, a sub-category of self-employed persons, known as 'employee-like' persons, is also included in the scope of the statute on collective agreements. For all other self-employed persons, however, no such statutory inclusion exists. They are, rather, prevented from collective price setting by (national und EU) competition law. Upon a closer look at the social purpose of exempting collective agreements from the restrictions of competition law, it is necessary to differentiate according to the existence of a structural power imbalance to the detriment of one contracting party much rather than according to the type of contract concluded. Some self-employed persons, specifically those categorised as workers under a new form of employment, do need collective bargaining as much as employees do, as they find themselves in a comparably weak individual bargaining position.